Interleukin-1 links autoimmune and autoinflammatory pathophysiology in mixed-pattern psoriasis - Kölliker Frers, Rodolfo (2021)
Fil: Kölliker Frers, Rodolfo. Universidad Abierta Interamericana. Centro de Altos Estudios en Ciencias Humanas y de la Salud; Argentina